Screenos cookbook - Brunner, Stefan (O'Reilly Media, 2008)
In the only book that completely covers ScreenOS, six key members of Juniper Network's ScreenOS development team help you troubleshoot secure networks using ScreenOS firewall appliances. Over 200 recipes address a wide range of security issues, provide step-by-step solutions, and include discussions of why the recipes work, so you can easily set up and keep ScreenOS systems on track. The easy-to-follow format enables you to find the topic and specific recipe you need right away.
Print version record
Keywords: Firewalls (Computer security); Computer networks -- Security measures; Coupe-feu (Sécurité informatique); Réseaux d'ordinateurs; Sécurité; Mesures; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures